TRANSLATION OF NATIONAL-CULTURAL CHRACTERISTICS IN TRANSLATION DICTIONARIES (Scientific journal of the Fergana State University, 2024)
The topic of national and cultural characteristics in translation dictionaries reflects the uniqueness of language, culture, and society. Language, through its original features, grammar, vocabulary, and expressions, conveys its core meanings. Meanwhile, culture encompasses spiritual values, literature, art, music, creativity, and other areas of the culture and art of a particular people or society. The reflection of national and cultural characteristics in translation dictionaries demonstrates the basic characteristics of the language, its unique formation, and specificity. This is an expression of the natural relations of a united society and shows them through cultural interaction. The topic of national and cultural characteristics in translation dictionaries is important in the field of education and teaching. National language features may vary and include expressions and words, as well as ways of interpreting them. For example, the ways of formation and the meaning of a specific word can reflect the style and cultural history of the national language. National and cultural characteristics are interrelated and convey to us historical, geographical, cultural, and other factors. This is extremely important for translation dictionaries, as understanding the meaning and characteristics of language requires studying its unique aspects.